The Issues of Islamic Education Teachers in Developing Professional Competence at SMP N 1 Pajar Bulan - Sari, Lara Purnama; Darma Sugiarta (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the issues faced by Islamic Education teachers in developing professional competence at SMP N 1 Pajar Bulan. The aim of this study is to understand the challenges faced by Islamic Education teachers in developing professional competence at SMP N 1 Pajar Bulan. This research uses a descriptive qualitative approach. The data collection techniques used include observation, documentation, and interviews with Islamic Education teachers and the curriculum coordinator. The results show that the Islamic Education teachers at SMP N 1 Pajar Bulan have performed their roles well and are recognized as professional teachers. Before receiving such recognition, Islamic Education teachers faced various challenges, such as limited facilities, time constraints, and personal obstacles. However, their strong enthusiasm and desire to continuously improve were key to their success. Support from colleagues, peers, and student involvement were also important factors in the development of professional competence. Students were found to have a significant impact on teacher quality, as the progress of both teachers and students are interrelated. Furthermore, the rapid advancement of knowledge and technology has encouraged Islamic Education teachers to continuously enhance their competencies to keep up with the times.